Bullying and cyberbullying : what every educator needs to know - Englander, Elizabeth Kandel (Cambridge, Mass. : Harvard Education Press, 2013)
'Bullying is a term that's being, well, bullied. It's been rendered essentially powerless by being constantly kicked around,' writes nationally recognized bullying expert Elizabeth Kandel Englander. In this practical and insightful book, Englander dispels pervasive myths and misconceptions about peer cruelty, bullying, and cyberbullying. Drawing on her own and others' research, she shows how educators can flag problematic behaviors and frame effective responses. Englander puts a special focus on'gateway' behaviors--those subtle actions that, unchecked, can quickly escalate into more serious misbehavior--and explores how students perceive their own and their peers' behavior. Written in an accessible, conversational tone and informed by careful research, this timely book is an essential guide for educators. Key takeaways include the impact of technology on social behavior, a framework for responding effectively to bullies--including innovative ideas about the role of social peers--and suggestions for working with parents. -- Publisher description.
Introduction: The bullying enigma -- The new face of bullying : understanding'gateway behaviors' -- How common are bullying and cyberbullying, anyway? : parsing the numbers to identify--and help--children at risk -- Why do children bully and cyberbully? : the impact of digital technology on social behavior -- How bullying and cyberbullying interact : the amplification of conflict in cyberspace -- New times, new troubles : sexting, self-cyberbullying, and other risky online behaviors -- Responding effectively to bullying : the'9-second response' and other informal and formal strategies -- Engaging bystanders and other peers : a developmental approach to cultivating prosocial behavior -- Working with parents : shared goals, different perspectives -- Conclusion: Moving the field forward -- Appendix A: Research discussed in this book -- Appendix B: The Massachusetts Aggression Reduction Center.
Includes bibliographical references and index.
Keywords: Cyberbullying; Bullying; Bullying in schools; Internet and children